Temperature dependent mechanical properties of graphene reinforced polymer nanocomposites – A molecular dynamics simulation - Lin, Feng; Xiang, Y.; Shen, Hui-Shen (Composites. Part B, Engineering, 2017)
This paper investigates the mechanical properties of graphene/PMMA nanocomposite system by using the molecular dynamics simulations. The graphene nanoplates are assumed to be fully exfoliated in the PMMA matrix and are all planar orientated, which are similar to the ones assembled using layer-by-layer technique. The Young's modulus and shear modulus of the composites with different graphene volume fractions under different temperatures are simulated and discussed. The results show that the Young's and shear moduli increase with the increase of graphene volume fraction and decrease as the temperature rises from 300 K to 500 K, while the efficiency of the reinforcement is reduced as the graphene content becomes higher. Simulations of single layer graphene under uniaxial tension, in-plane pure shear and uniformly distributed transverse load are performed and the effective thickness and the elastic moduli of graphene are subsequently determined uniquely. The obtained stiffnesses of graphene are then substituted into the simple rule of mixture to predict the overall mechanical properties of the composite. Large discrepancies between the results from the MD simulations and the rule of mixture are observed. •The mechanical properties of graphene reinforced nanocomposites are obtained by MDS.•The material properties of graphene reinforced nanocomposites are temperature dependent.•The conventional rule of mixture cannot be used directly for the graphene reinforced nanocomposites.